2020
DOI: 10.1016/j.buildenv.2020.107149
|View full text |Cite
|
Sign up to set email alerts
|

Effect of equipment layout on bioaerosol temporal-spatial distribution and deposition in one BSL-3 laboratory

Abstract: Reasonable equipment layout is essential for creating a healthy and safe environment, especially in a three-level biosafety laboratory with high potential risk factors of infection. Since 2019, COVID-19, an emerging infection has swept the world and caused severe losses. Biosafety laboratories are mandatory sites for detecting high-risk viruses, so related research is urgently needed to prevent further laboratory-acquired infections of operators. This study investigated the effects of obstacles on exposure inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The deposition rate of bioaerosols on the ceiling and walls was substituted by a percentage equal to 23% and 44% of the deposited microorganisms' concentration on the floor, respectively, based on Liu et al 18 Although this is an estimation and it allows for biased results because the inlet and outlet for ventilation for Liu et al 18 were located in the ceiling, which may change the surface deposition pattern. Assuming that the floor and the ceiling have the same surface area, Equation 5 uses the same principle as Equation 3 and calculates the loss rate due to deposition, taking into account the deposition onto the walls and ceiling as a percentage of the deposition on the floor (based on real data from the experiment).λdgoodbreak=λd,fgoodbreak+βwλd,f2H)(Lgoodbreak+WLWgoodbreak+βcλd,f,$$ {\lambda}_d={\lambda}_{d,f}+{\beta}_w{\lambda}_{d,f}\frac{2H\left(L+W\right)}{LW}+{\beta}_c{\lambda}_{d,f}, $$Where, βw$$ {\beta}_w $$ and βc$$ {\beta}_c $$ are the percentages of Csf$$ {C}_{sf} $$, which is the indoor deposited microorganisms' concentration on the floor (italiccfu.m2.h1$$ cfu.{m}^{-2}.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The deposition rate of bioaerosols on the ceiling and walls was substituted by a percentage equal to 23% and 44% of the deposited microorganisms' concentration on the floor, respectively, based on Liu et al 18 Although this is an estimation and it allows for biased results because the inlet and outlet for ventilation for Liu et al 18 were located in the ceiling, which may change the surface deposition pattern. Assuming that the floor and the ceiling have the same surface area, Equation 5 uses the same principle as Equation 3 and calculates the loss rate due to deposition, taking into account the deposition onto the walls and ceiling as a percentage of the deposition on the floor (based on real data from the experiment).λdgoodbreak=λd,fgoodbreak+βwλd,f2H)(Lgoodbreak+WLWgoodbreak+βcλd,f,$$ {\lambda}_d={\lambda}_{d,f}+{\beta}_w{\lambda}_{d,f}\frac{2H\left(L+W\right)}{LW}+{\beta}_c{\lambda}_{d,f}, $$Where, βw$$ {\beta}_w $$ and βc$$ {\beta}_c $$ are the percentages of Csf$$ {C}_{sf} $$, which is the indoor deposited microorganisms' concentration on the floor (italiccfu.m2.h1$$ cfu.{m}^{-2}.…”
Section: Resultsmentioning
confidence: 99%
“…The deposition rate of bioaerosols on the ceiling and walls was substituted by a percentage equal to 23% and 44% of the deposited microorganisms' concentration on the floor, respectively, based on Liu et al 18 Although this is an estimation and it allows for biased results because the inlet and outlet for ventilation for Liu et al 18 were located in the ceiling, which may change the surface deposition pattern. Assuming that the floor and the ceiling have the same surface area, Equation 5 uses the same principle as Equation 3 and calculates the loss rate due to deposition, taking into account the deposition onto the walls and ceiling as a percentage of the deposition on the floor (based on real data from the experiment).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on these three ventilation strategies, the effects of different air supply inlets in isolation ward on bioaerosol deposition, spatial distribution and removal efficiency were studied. Our previous research found that facility layout may influence aerosol distribution [35] . Therefore, two scenarios were considered: empty room and actual room.…”
Section: Case Studymentioning
confidence: 99%
“…However, this study will look at droplets across an entire distribution. A lab study found that equipment layout stopped 17% of pollutant particles' effective discharge since they lingered under vortex influence ( Liu et al., 2020 ). However, this will not be included in this paper's scope since worker dorms do not have much equipment except for their personal belongings and bed structures, which are included in this study.…”
Section: Introductionmentioning
confidence: 99%